Penguatan Kompetensi Digital Berstandar Microsoft Office Specialist (MOS) bagi Guru MA Annida Al-Islamy - Luqman; Hendra Jatnika; Rakhmadi Irfansyah Putra; Yudhi Setyo Purwanto; Ocha Nia Martcya Situmorang; M. Rafif Soniansyah; Fakhri Faros (Politeknik Piksi Ganesha Indonesia, 2026)
This Community Service program aims to strengthen the digital competence of teachers at MA Annida Al-Islamy through Microsoft Office Specialist (MOS) certification preparation. The primary issue identified was the basic level of office application mastery, which fell below global standards. The method involved preliminary surveys, needs analysis, material preparation, hands-on technical workshops based on participant interests (Word, Excel, PowerPoint), and evaluation. Results from 15 participants showed significant success, with an average perceived competence improvement of 92.4%. Additionally, over 85% of technical challenges during trivia sessions were answered correctly. Program outputs, including digital modules and video tutorials, were provided to support sustainable self-paced learning. This training effectively enhanced educators' technical readiness and confidence in meeting international competency standards.